Homologous recombination suppresses transgenerational DNA end resection and chromosomal instability in fission yeast. Issue 7 (23rd March 2023) - Pai, Chen-Chun; Durley, Samuel C; Cheng, Wei-Chen; Chiang, Nien-Yi; Peters, Jennifer; Kasparek, Torben; Blaikley, Elizabeth; Wee, Boon-Yu; Walker, Carol; Kearsey, Stephen E; Buffa, Francesca; Murray, Johanne M; et al.
Abstract: Chromosomal instability (CIN) drives cell-to-cell heterogeneity, and the development of genetic diseases, including cancer. Impaired homologous recombination (HR) has been implicated as a major driver of CIN, however, the underlying mechanism remains unclear. Using a fission yeast model system, we establish a common role for HR genes in suppressing DNA double-strand break (DSB)-induced CIN. Further, we show that an unrepaired single-ended DSB arising from failed HR repair or telomere loss is a potent driver of widespread CIN. Inherited chromosomes carrying a single-ended DSB are subject to cycles of DNA replication and extensive end-processing across successive cell divisions. These cycles are enabled by Cullin 3-mediated Chk1 loss and checkpoint adaptation. Subsequent propagation of unstable chromosomes carrying a single-ended DSB continues until transgenerational end-resection leads to fold-back inversion of single-stranded centromeric repeats and to stable chromosomal rearrangements, typically isochromosomes, or to chromosomal loss. These findings reveal a mechanism by which HR genes suppress CIN and how DNA breaks that persist through mitotic divisions propagate cell-to-cell heterogeneity in the resultant progeny.